Physico-chemical Characterization of Waterlogged Archaeological Wood from a Charred Medieval Shipwreck - Μήτση, Ειρήνη (Πανεπιστήμιο Πελοποννήσου, 2023)
In 2008, a partially burned wooden shipwreck, dating from the 12th century, was discovered off the port of Rhodes, Greece. The shipwreck timbers presented a varied degree of charring consisting of uncharred, charred and semi-charred material, often encountered on the same piece of wood, which indicates considerably different consolidation requirements and poses a great challenge for their future conservation. This study was set to characterize the morphology, and the physical, chemical and mechanical properties of the material, in order to assist in the development of an appropriate remedial conservation strategy. The morphology of the archaeological wood was documented via scanning electron microscopy (SEM). The main physical properties were estimated gravimetrically whereas its porosity was evaluated by mercury intrusion porosimetry (MIP). For the charred and the semi-charred wood, proximate analysis was also undertaken. The mechanical properties were investigated using a modified Janka test and a fruit penetrometer. The chemistry of wood was examined with Fourier transform infrared spectroscopy (FTIR) for the organic part of wood, and energy dispersive spectroscopy (EDS) for its inorganic composition. Alterations on cellulose crystallinity were also assessed with X-ray diffraction (XRD). Results regarding the morphology, clearly demonstrated the three distinct charring degrees of the material that exhibited significant ultrastructural differences, although the basic cellular anatomy of wood had been preserved. More specifically, the uncharred material showed signs of severe biodeterioration which is typical in waterlogged wood, while the semi-charred and charred wood exhibited alterations mainly owed to thermal exposure rather than bacterial or fungal decay. In addition, the semi-charred samples presented a varied degree of thermal degradation, reflecting its diverse exposure to the fire front, whereas the charred material presented “plastic deformation” that indicated fast pyrolysis of a wet wood, at high temperatures. Physical properties confirmed that the exposure of wood to heat and its burial in the marine environment, has created three different waterlogged “materials”. In particular among the three charring conditions, the uncharred wood presented the lowest basic density, the highest shrinkage and an increased porosity mainly due to biodeterioration. In contrast, the semi-charred and the charred wood presented extremely low shrinkage, which was even lower than sound wood of the same species, whereas their porosity was only slightly increased. All three charring conditions showed low hardness compared to sound wood, attributed either to biodeterioration or/and to thermal degradation. Furthermore, hardness values of the semi-charred wood were in accordance with the morphological observations, showing the transitional nature of the material, extending from the charred to the uncharred zone. The results obtained regarding the residual chemistry of the material were highly correlated with its physico-mechanical properties and its morphology. Uncharred wood was found to be chemically similar to biodeteriorated wood, with depleted carbohydrates, increased relative lignin content, and elevated sulfur and iron concentrations. The semi-charred material presented a chemical profile comparable to thermally modified wood where hemicelluloses were reduced, cellulose crystallinity was increased, and lignin was not significantly altered compared to sound wood. In contrast in charred wood, polysaccharides and lignin were almost absent due to pyrolysis, making its organic chemistry similar to charcoals. The inorganic chemistry of the wood exposed to the fire showed that, towards the charred areas, sulfur, iron and oxygen concentrations were decreasing, while the carbon content was increasing. Based on the results of the present study, it is evident that uncharred wood requires remedial conservation using consolidants, whereas semi-charred and charred wood may be left to air-dry without treatment. Nevertheless, a great challenge arises for conservators as the three charring conditions often coexist and the low porosity of the outer charred layer is not expected to facilitate the penetration of consolidants into the uncharred core of wood and impede its consolidation.
Keywords: Ξύλο -- Χημεία; Ξύλο -- Έλεγχος; Ξύλο -- Ανατομία; Άνθρακας -- Ανάλυση; Ηλεκτρονική μικροσκοπία σάρωσης; Χημεία, Οργανική -- Μεθοδολογία; Φασματοσκοπία; Η περίθλαση ακτίνων-Χ; Αρχαιολογική χημεία; Αρχαιότητες -- Ανάλυση; Αρχαιολογία -- Μεθοδολογία; Ξύλο -- Διατήρηση -- Ελλάδα -- Ρόδος (Νησί); Ξύλο -- Συντήρηση και αποκατάσταση; Πλοία, Ξύλινα -- Ελλάδα -- Ρόδος (Νησί); Πλοία, Μεσαιωνικά -- Ελλάδα -- Ρόδος (Νησί); Ναυάγια -- Ελλάδα -- Ρόδος (Νησί); Πολιτιστική κληρονομιά -- Προστασία -- Ελλάδα -- Ρόδος (Νησί); Ρόδος (Νησί, Ελλάδα) -- Αρχαιότητες -- Συντήρηση και αποκατάσταση; Waterlogged archaeological wood; Charred wood; Physical properties; Mercury intrusion porosimetry (MIP); Proximate analysis; Janka hardness; Scanning electron microscopy (SEM); Energy dispersive spectroscopy (EDS); Fourier transform infrared spectroscopy (FTIR); X-ray diffraction (XRD); Ένυδρο αρχαιολογικό ξύλο; Απανθρακωμένο ξύλο; Φυσικές ιδιότητες; Ποροσιμετρία υδραργύρου (MIP); Προσεγγιστική ανάλυση; Σκληρότητα Janka; Ηλεκτρονική μικροσκοπία σάρωσης (SEM); Φασματοσκοπία ενεργειακής διασποράς (EDS); Φασματοσκοπία υπερύθρου μετασχηματισμού Fourier (FTIR); Περίθλαση ακτίνων X (XRD)